1986
DOI: 10.1029/tc005i004p00629
|View full text |Cite
|
Sign up to set email alerts
|

Seismic evidence for conjugate slip and block rotation within the San Andreas Fault System, southern California

Abstract: The pattern of seismicity in southern California indicates that much of the activity is presently occurring on secondary structures, several of which are oriented nearly orthogonal to the strikes of the major through-going faults. Slip along these secondary transverse features is predominantly left-lateral and is consistent with the reactivation of conjugate faults by the current regional stress field. Near the intersection of the San Jacinto and San Andreas faults, however, these active left-lateral faults ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(64 citation statements)
references
References 55 publications
3
61
0
Order By: Relevance
“…This agrees well with the findings of Mendoza and Hartzell (1988), who made similar observations looking at aftershock patterns and mainshock faulting associated with a number of earthquakes in California andIdaho between 1966 and1986. This characteristic is also consistent with the conclusions of Liu et al (1999Liu et al ( , 2003, that most of the aftershocks of the 1992 Landers earthquake are not candidates for rerupture of the mainshock faults, and of Rubin and Gillard (2000), who showed that aftershocks of microearthquakes on the central SAF tend not to occur within a distance approximately equal to the radius of the first rupture.…”
Section: Spatial Distributionsupporting
confidence: 82%
See 1 more Smart Citation
“…This agrees well with the findings of Mendoza and Hartzell (1988), who made similar observations looking at aftershock patterns and mainshock faulting associated with a number of earthquakes in California andIdaho between 1966 and1986. This characteristic is also consistent with the conclusions of Liu et al (1999Liu et al ( , 2003, that most of the aftershocks of the 1992 Landers earthquake are not candidates for rerupture of the mainshock faults, and of Rubin and Gillard (2000), who showed that aftershocks of microearthquakes on the central SAF tend not to occur within a distance approximately equal to the radius of the first rupture.…”
Section: Spatial Distributionsupporting
confidence: 82%
“…(In the 1979 earthquake, which involved rupture on the Brawley fault and the Imperial fault south to the international border, the intensity was uniformly MMI VII from Brawley to Calexico; see Reagor et al [1982] and Nason [1982].) Alternatively, slip along one of the northeast-trending cross faults southeast of the Salton Sea could be responsible; candidates include the fault involved in the strongest aftershock of the 1979 event (Johnson and Hutton, 1982) and the fault involved in the 1981 Westmorland earthquake (Nicholson et al, 1986 (Gurrola and Rockwell, 1996). We also rule out a location on the SAF near or northwest of Bombay Beach because Bombay Beach is approximately halfway between Brawley and Coachella, but the intensities are much higher in Brawley and to the south than they are in Coachella and to the north.…”
Section: April 1906 Santa Cruz Area Aftershockmentioning
confidence: 99%
“…A variety of fault geometries, including flower structures (e.g., where complex surface faults coalesce onto simpler structures at depth) and conjugate faulting (e.g., where complex surface faults remain individual planes at depth) have been previously identified along major strike-slip faults. Weldon II et al [2002] and Harding [1985,1988] observe active flower structures along the San Andreas fault and other prominent strike-slip faults in Southern California, while Sharp [1967], Nicholson et al [1986], and Hauksson et al [2002] suggest that conjugate faulting is common in immature fault systems. Here multiple planar faults that extend the full depth of the seismogenic zone are apparent in three-dimensional visualizations of the relocated seismicity.…”
Section: A Complex Network Of Conjugate Faultsmentioning
confidence: 99%
“…perial fault. The BSZ is a diffuse zone of seismicity that extends north-northwest from the BFZ toward the San Andreas fault (SAF) at Bombay Beach; focal mechanisms and seismicity lineaments within the BSZ indicate that most of the earthquakes occur on left-lateral northeast-trending and right-lateral northwest-trending cross-faults (e.g., Fuis et al, 1982;Nicholson et al, 1986;P. Shearer, unpublished data).…”
Section: Introductionmentioning
confidence: 99%